The Influence of Greenwashing Perception and Transparency Disclosure on Consumer Trust in FMCG Products in Jakarta - Andriya Risdwiyanto; Rival Pahrijal; Rani Eka Arini (West Science Social and Humanities Studies, 2026)
This study aims to analyze the effect of perceptions of greenwashing and transparency in information disclosure on consumer trust in Fast-Moving Consumer Goods (FMCG) products in Jakarta. Increasing environmental awareness among consumers has encouraged FMCG companies to adopt green marketing strategies; however, misleading environmental claims may reduce consumer confidence toward environmentally oriented products. This research employed a quantitative approach using a survey method involving 150 respondents in Jakarta who had purchased FMCG products with environmental claims. Data were collected using questionnaires measured with a Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results indicate that perceptions of greenwashing have a negative and significant effect on consumer trust, while transparency in information disclosure has a positive and significant effect on consumer trust. The findings demonstrate that consumers tend to distrust companies perceived as exaggerating or manipulating environmental claims, whereas transparent and honest sustainability communication strengthens consumer confidence. The study concludes that FMCG companies should avoid deceptive green marketing practices and improve transparency in environmental information disclosure to maintain and enhance consumer trust. These findings provide theoretical contributions to green marketing literature and practical implications for companies seeking to strengthen sustainability-based competitive advantages in urban consumer markets.